Удосконалення мотивування працівників вітчизняних підприємств на засадах впровадження системи грейдів - Мельник, О. Г.; Денисюк, О. В.; Григор’єв, О. Ю. (Видавництво Львівської політехніки, 2015)
Обґрунтовано, що система мотивування, сформована на підприємстві, має важливе значення у досягненні бажаних цілей діяльності компанії, безпосередньо впливає на фінансову результативність. Запропоновано використовувати сучасні підходи до управління, зокрема й до мотивування праці. Висвітлено основні теоретичні аспекти системи грейдів, запропоновано трактувати систему грейдів як метод формування якісної системи мотивування створенням універсальної ієрархії посад, системи адекватної оцінки власних працівників та оплати праці згідно з виконуваними функціями, міри відповідальності, кількості осіб в підпорядкуванні. На підставі виконаних досліджень обґрунтовано принципи, на засадах яких здійснюється система мотивування та основні передумови її впровадження на вітчизняних підприємствах, а також проблеми, які можуть виникнути від невчасного реагування на виклики сучасного ринку. Виокремлено переваги та недоліки системи грейдів, описано основні етапи її реалізації. It is a well-known fact that Ukrainian labor market is in the process of radical transformation. There are high levels of unemployment and the most unattractive conditions of remuneration and outflow of skilled workers abroad. This slows the development of a motivation system, because for a lot of people work doesn’t mean a personal development or realization of their own potential, but they are working to survive. This causes that employers establish an unacceptable rules, forcing staff to work in the unfavorable environment. They manipulate human resources and offsetting the cost by paying the established minimum national standards. In the context of limited resources there are various types of skilled, talented and creative workers that are able to create new competitive advantages, to make unconventional decisions and develop innovations. In such circumstances, there is a need to implement effective tools to motivate employees, one of that tools is the grade system that enables you to ensure transparent and fair distribution of wages depending on the characteristics of office workers. The main objective is to develop the mechanism for implementation and usage of the grade system in the modern business environment for domestic enterprises. Our tasks include: – clarifying the concept of “grade system”, justify motivational role of it, identify the advantages and disadvantages of the grade system; – identifying prerequisites for introducing grade system for domestic enterprises; – developing a mechanism for implementing and adapting grade system at domestic enterprises. The article proved that the system of motivation, that formed by the company plays an important role in achieving the desired objectives of the company and directly affects the financial results and increases the motivation of workers. It is advisable to learn, adapt and apply new approaches to management. The investigations allow to single out the following main conditions for the development grade system in Ukraine: opacity of wage system and low size of salary; lack of mechanisms which monitor the effectiveness of salaries; salary for new employeers are unreasonably higher than for long working staff; transparent communication about compensation; manual control of payroll; excessive tax burden and others.
Improvement of employees motivation in domestic enterrises on the basis of implementation of the grade system
Keywords: грейд; грейдова система; мотивування; оплата праці; посада; Grade; grade system; motivation; salary; work position